POSICIÓN SISTEMÁTICA Y REDESCRIPCIÓN DE SCAPTIA (PSEUDOMELPIA) HORRENS ENDERLEIN, 1925 (DIPTERA: TABANIDAE: PANGONIINAE) - Coscaron, S.; González, C. R. (Acta Entomológica Chilena, 2022)
The subgenus Pseudomelpia Enderlein composed by only one known species from Southern Chile is redefined, and a new key and comments for subgenera of Scaptia Walker of Australasian and Neotropical distribution is offered.